Legal Review of Termination of Prosecution of Drug Abusers Based on Restorative Justice (Case Study of Bengkalis District Attorney's Office) - Sitanggang, Marulitua Johannes; Laksana, Andri Winjaya (UNISSULA Semarang, 2025)
The practice of legal policy in Indonesia, as part of the national legal policy in resolving narcotics crime cases, still positions the actions committed by narcotics abusers as serious crimes that must be punished with criminal sanctions. The purpose of this research is to examine and analyze the implementation of prosecution termination by the Prosecutor's Office against narcotics addicts through a restorative justice approach, and to examine and analyze the obstacles in the implementation of such prosecution termination along with the proposed solutions. This legal research uses an empirical legal research method. Empirical juridical research is legal research that applies legal principles and doctrines to review, observe, and analyze legal issues, while also assessing the implementation of the law in practice. The implementation of prosecution termination by the Prosecutor's Office against narcotics addicts through a restorative justice approach is a progressive step that emphasizes rehabilitation and recovery rather than punishment. Its legal basis includes the Prosecutor's Regulation of the Republic of Indonesia Number 18 of 2021 and Article 127 of the Narcotics Law, which recognizes addicts as victims who deserve medical and social rehabilitation. This approach also aims to reduce prison overcrowding and break the chain of drug distribution through selective handling and inter-institutional collaboration. However, the approach faces challenges in terms of unsynchronized legal substance, weak structural coordination, and cultural resistance, including public stigma. Proposed solutions include regulatory harmonization, enhanced prosecutorial capacity, strengthened rehabilitation facilities, and public anti-stigma campaigns. As part of long-term legal reform, the decriminalization of narcotics users is also considered important to shift the legal approach from punitive to a more humane and health-oriented model.